Nalar Ekologi Dalam Perspektif Islam - Saefullah Saefullah (Jurnal Penelitian, 2016)
Problems of the environment now show an alarming rate. Various facts environmental destruction on Earth has made its inhabitants disturbed. This paper seeks patterned library research and browse for Islamic contribution in solving this problem. As a result, Islam gives a great attention to the various problems of human life, including the environment. This formulation is different from Western modernist views of scientists who tend to use a technical approach only, without looking at other aspects. In fact, using a technical approach alone is not sufficient, but it also requires other approaches, including the transcendent and profane.